HUBUNGAN DUKUNGAN SUAMI DAN DUKUNGAN KELUARGA DENGAN PEMBERIAN ASI EKSKLUSIF PADA IBU ANGGOTA KELOMPOK PENDUKUNG ASI (KP-ASI) - Ona Oktalina; Lailatul Muniroh; Sri Adiningsih (Universitas Airlangga, 2015)
Breast milk is the best investment for children’s health and intelligence of. Exclusive breastfeeding is influenced by health behavior factors, one of which is a driving factor including husband and family support that is necessary for mothers to breastfeed exclusively. The purpose of this study was to analyze the relationship between husband and family support with exclusive breastfeeding in breastfed mothers of KP-ASI members in Megaluh Jombang Public Health Center. This study is an observational analytic study with cross sectional design. Sample was breastfed mother who is participant of KP-ASI and had infants aged 6-12 months as much as 74 people selected using purposive sampling method. The data was collected through interview using a questionnaire. The result showed there was a correlation between family support and exclusive breastfeeding behavior (p = 0.011) but there was no correlation between husband support with exclusive breastfeeding behavior (p = 0.090). In conclusion, family support as reinforcing factor can motivate a mother to do exclusive breastfeeding. It is expected that all members of the family can provide support for mother to breastfeed exclusively and cadres can also invite mothers’ family members (parents, husband, siblings) to participate in the counseling (KP-ASI) activity and provide education regarding the importance of exclusive breastfeeding.Keywords: breastfeeding behavior, exclusive breastfeeding, family support, husband support